A current design approach for Ming chairs - Yifan, Bai; Kamarudin, Khairul Manami; Alli, Hassan (MDPI, 2024)
Ergonomics are key in the design and application of Ming-style chairs. However, there are presently few specific design frameworks to guide Ming-style chair design. Under this background, the present study developed a questionnaire on the ergonomic design of Ming-style chairs and assessed its validity and reliability. Fifty-two respondents involved in the design and manufacture of Ming-style chairs participated in this study. The statistics of the questionnaire were analyzed and yielded a significant reliability coefficient (α > 0.70, p < 0.01). This ergonomic design framework study of Ming-style chairs analyzed the domains of Chair Form, Aesthetics, Safety, Comfort, Ease-of-use, and Productivity. To assess the importance of various design elements, we used a five-point Likert scale to score items within each domain. This scoring system enabled us to prioritize features, allowing the designers to focus on the essential elements before beginning the design process. We found that designers and manufacturers focused primarily on the Four-headed Official Chair with Armrests form.